Analisis Penerimaan Aplikasi Mobile JKN Menggunakan Model Unified Theory of Acceptance And Use of Technology 3 di DKI Jakarta - Mochamad Ichrom Tobari; Sarah Geltri Harahap; Enni Juliani (jitek, 2026)
The success of information technology-based services is largely determined by the acceptance and willingness of the community to use them. One such digital service provided by the government through BPJS Kesehatan is the Mobile JKN application. designed to facilitate access to health services for JKN participants online. Community participation. especially in DKI Jakarta with its urban characteristics. plays a key role in the effectiveness of this service. This study aims to measure the level of acceptance of the Mobile JKN application in DKI Jakarta using the Unified Theory of Acceptance and Use of Technology 3 (UTAUT 3) model. The research uses purposive and proportional stratified sampling methods. involving 250 respondents who are users of the Mobile JKN application. Data were collected through online questionnaires and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Results show that performance expectancy (p = 0.014). social influence (p = 0.020). facilitating conditions (p = 0.010). habit (p = 0.025). and price value (p = 0.000) significantly influence behavioral intention. Moreover. facilitating conditions (p = 0.044). habit (p = 0.000). personal innovativeness (p = 0.003). and behavioral intention (p = 0.001) significantly influence use behavior. Meanwhile. effort expectancy (p = 0.262). hedonic motivation (p = 0.632). and personal innovativeness (p = 0.080) do not significantly affect behavioral intention. The study recommends enhancing features. fostering innovation. and increasing outreach to improve application acceptance.